Haskell dot operator with sort and (++) [duplicate] - haskell

This question already has answers here:
Haskell function composition operator of type (c→d) → (a→b→c) → (a→b→d)
(6 answers)
Closed last year.
I am learning haskell at the moment and trying to figure out all the rules of prefix, infix, precedence, etc.
While trying to implement a function which appends two lists and sorts them I started with:
appendAndSort :: [a] -> [a] -> [a]
appendAndSort = sort . (++)
which does no compile.
Following:
appendAndSort :: Ord a => [a] -> [a] -> [a]
appendAndSort = (sort .) . (++)
on the other hand does work.
Why do I have to add a second dot at sort and parentheses around it?

Let's start with a version that uses explicit parameters.
appendAndSort x y = sort (x ++ y)
Writing ++ as a prefix function rather than an operator yields
appendAndSort x y = sort ((++) x y)
Knowing that (f . g) x == f (g x), we can identify f == sort and g == (++) x to get
appendAndSort x y = (sort . (++) x) y
which lets us drop y as an explicit parameter via eta conversion:
appendAndSort x = sort . (++) x
The next step is to repeat the process above, this time with (.) as the top most operator to write as a prefix function,
appendAndSort x = (.) sort ((++) x)
then apply the definition of . again with f == (.) sort and g == (++):
appendAndSort x = (((.) sort) . (++)) x
and eliminate x via eta conversion
appendAndSort = ((.) sort) . (++)
The last step is to write (.) sort as an operator section, and we're done with our derivation.
appendAndSort = (sort .) . (++)

The expression (f . g) x means f (g x).
Coherently, (f . g) x y means f (g x) y.
Note how y is passed as a second parameter to f, not to g. The result is not f (g x y).
In your case, (sort . (++)) x y would mean sort ((++) x) y, which would call sort with first argument (++) x (the function which prepends the list x to its list argument), and with second argument y. Alas, this is ill-typed since sort only takes one argument.
Consequently, this is also invalid
appendAndSort x y = (sort . (++)) x y
hence so is this
appendAndSort = sort . (++)
By contrast, ((f .) . g) x y does work as expected. Let's compute:
((f .) . g) x y
= -- same reasoning as above, y is passed to (f.), not g
(f .) (g x) y
= -- application associates on the left
((f .) (g x)) y
= -- definition of `(f.)`
(f . (g x)) y
= -- definition of .
f ((g x) y)
= -- application associates on the left
f (g x y)
So this really makes y to be passed to g (and not f).
In my opinion the "idiom" (f .) . g isn't worth using. The pointful \x y -> f (g x y) is much simpler to read, and not terribly longer.
If you really want, you can define a custom composition operator to handle the two-argument case.
(.:) f g = \x y -> f (g x y)
Then, you can write
appendAndSort = sort .: (++)

Related

Point free style with infix notation

Hello is there a way to write point free style when using infix notation?
f::Int->Int->Int->Int
f a b=(+) (a+b)
Why you cannot do something like this ?
f::Int->Int->Int->Int
f a b=(a+b) +
or
f a b= (a+b) `+`
Can you not combine operators in point free style like e.g?
ptfree::Int->Int->Int->Int
ptfree=(+) (+)
I mean you can chop arguments of functions like fold but why not for operator arguments?
Well since you need to pass two parameters, we can use what is known as the "surprised owl operator". This is basically a composition of parameters. So we can use:
f = ((.).(.)) (+) (+)
Or we can more inline the operator like:
f = ((+) .) . (+)
The owl operator ((.).(.)) f g basically is short for \x y -> f (g x y)
How does this work?
The canonical form of the "surprised owl operator" is:
= ((.) . (.))
------------- (canonical form)
(.) (.) (.)
So we can now replace the (.)s with corresponding lambda expressions:
(\f g x -> f (g x)) (.) (.)
So now we can perform some replacements:
(\f g x -> f (g x)) (.) (.)
-> (\x -> (.) ((.) x))
-> (\x -> (\q r y -> q (r y)) ((.) x))
-> (\x -> (\r y -> ((.) x) (r y)))
-> (\x r y -> ((.) x) (r y))
-> (\x r y -> ((\s t u -> s (t u)) x) (r y))
-> (\x r y -> (\t u -> x (t u)) (r y))
-> (\x r y -> (\u -> x ((r y) u)))
-> \x r y u -> x ((r y) u))
-> \x r y u -> x (r y u)
So basically it means that our surprised owl operator, is equal to:
surprised_owl :: (y -> z) -> (a -> b -> y) -> a -> b -> z
surprised_owl f g x y = f (g x y) -- renamed variables
And if we now specialize this with the fuctions provided (two times (+)), we get:
f = surprised_owl (+) (+)
so:
f x y = (+) ((+) x y)
You must compose (+) with (+) twice, for it to be completely point-free: f = ((+) .) . (+)
Recall that composition is defined as
(f . g) x = f (g x)
or, equivalently:
(f . g) = \x -> f (g x)
So, if you look at the composition f = ((+) .) . (+) and work backwards using the definition of (.):
f = ((+) .) . (+)
f = \x -> ((+) .) ((+) x) -- definition of (.)
f = \y -> (\x -> (+) (((+) x) y)) -- definition of (.)
f x y = (+) (((+) x) y) -- a simpler way to write this
f x y z = (+) (((+) x) y) z -- explicitly add in the final argument (eta expansion)
f x y z = ((+) x y) + z -- rewrite as infix
f x y z = (x + y) + z -- rewrite as infix
and you see we end up with what we started before we tried to make it point-free, so we know that this definition works. Going the other way through the steps above, roughly bottom-to-top, could give you an idea of how you might find such a point-free definition of a function like f.
When you "leave off" multiple arguments from the "end" like this, you usually must compose multiple times. Working through a few similar functions should help build intuition for this.
Note: I wouldn't generally recommend using this sort of point-free (when it complicates things) in production code.

Point Free problems in Haskell

I am trying to convert the following Haskell code to point free style, to no avail.
bar f g xs = filter f (map g xs )
I'm new to Haskell and any help would be great.
Converting to pointfree style can be done entirely mechanically, though it's hard without being comfortable with the fundamentals of Haskell syntax like left-associative function application and x + y being the same as (+) x y. I will assume you are comfortable with Haskell syntax; if not, I suggest going through the first few chapters of LYAH first.
You need the following combinators, which are in the standard library. I have also given their standard names from combinator calculus.
id :: a -> a -- I
const :: a -> b -> a -- K
(.) :: (b -> c) -> (a -> b) -> (a -> c) -- B
flip :: (a -> b -> c) -> (b -> a -> c) -- C
(<*>) :: (a -> b -> c) -> (a -> b) -> (a -> c) -- S
Work with one parameter at a time. Move parameters on the left to lambdas on the right, e.g.
f x y = Z
becomes
f = \x -> \y -> Z
I like to do this one argument at a time rather than all at once, it just looks cleaner.
Then eliminate the lambda you just created according to the following rules. I will use lowercase letters for literal variables, uppercase letters to denote more complex expressions.
If you have \x -> x, replace with id
If you have \x -> A, where A is any expression in which x does not occur, replace with const A
If you have \x -> A x, where x does not occur in A, replace with A. This is known as "eta contraction".
If you have \x -> A B, then
If x occurs in both A and B, replace with (\x -> A) <*> (\x -> B).
If x occurs in just A, replace with flip (\x -> A) B
If x occurs in just B, replace with A . (\x -> B),
If x does not occur in either A or B, well, there's another rule we should have used already.
And then work inward, eliminating the lambdas that you created. Lets work with this example:
f x y z = foo z (bar x y)
-- Move parameter to lambda:
f x y = \z -> foo z (bar x y)
-- Remember that application is left-associative, so this is the same as
f x y = \z -> (foo z) (bar x y)
-- z appears on the left and not on the right, use flip
f x y = flip (\z -> foo z) (bar x y)
-- Use rule (3)
f x y = flip foo (bar x y)
-- Next parameter
f x = \y -> flip foo (bar x y)
-- Application is left-associative
f x = \y -> (flip foo) (bar x y)
-- y occurs on the right but not the left, use (.)
f x = flip foo . (\y -> bar x y)
-- Use rule 3
f x = flip foo . bar x
-- Next parameter
f = \x -> flip foo . bar x
-- We need to rewrite this operator into normal application style
f = \x -> (.) (flip foo) (bar x)
-- Application is left-associative
f = \x -> ((.) (flip foo)) (bar x)
-- x appears on the right but not the left, use (.)
f = ((.) (flip foo)) . (\x -> bar x)
-- use rule (3)
f = ((.) (flip foo)) . bar
-- Redundant parentheses
f = (.) (flip foo) . bar
There you go, now try it on yours! There is not really any cleverness involved in deciding which rule to use: use any rule that applies and you will make progress.
Both of the existing answers don't really answer your specific question in a way that's elucidating: one is "here are the rules, work it out for yourself" and the other is "here is the answer, no information about how the rules generate it."
The first three steps are really easy and consist in removing a common x from something of the form h x = f (g x) by writing h = f . g. Essentially it's saying "if you can write the thing in the form a $ b $ c $ ... $ y $ z and you want to remove the z, change all the dollars to dots, a . b . c . ... . y:
bar f g xs = filter f (map g xs)
= filter f $ (map g xs)
= filter f $ map g $ xs -- because a $ b $ c == a $ (b $ c).
bar f g = filter f . map g
= (filter f .) (map g)
= (filter f .) $ map $ g
bar f = (filter f .) . map
So this last f is the only tricky part, and it's tricky because the f is not at the "end" of the expression. But looking at it, we see that this is a function section (. map) applied to the rest of the expression:
bar f = (.) (filter f) . map
bar f = (. map) $ (.) $ filter $ f
bar = (. map) . (.) . filter
and that's how you reduce an expression when you don't have complicated things like f x x and the like appearing in it. In general there is a function flip f x y = f y x which "flips arguments"; you can always use that to move the f to the other side. Here we have flip (.) map . (.) . filter if you include the explicit flip call.
I asked lambdabot, a robot who hangs out on various Haskell IRC channels, to automatically work out the point-free equivalent. The command is #pl (pointless).
10:41 <frase> #pl bar f g xs = filter f (map g xs )
10:41 <lambdabot> bar = (. map) . (.) . filter
The point free version of bar is:
bar = (. map) . (.) . filter
This is arguably less comprehensible than the original (non-point-free) code. Use your good judgement when deciding whether to use point-free style on a case-by-case basis.
Finally, if you don't care for IRC there are web-based point-free
converters such as pointfree.io, the pointfree command line program, and other tools.

Applying multiple functions to the same value point-free style in Haskell

I was bored one day and wanted to exercise my brain, so I decided to do the 99 Haskell Problems but restricted myself to doing them in point-free style. A problem that seems to crop up a lot when I'm doing things in point-free style is this: How do you apply multiple functions to the same value while keeping each result as an independent entity? Using pointed notation:
foobar x = [id x, reverse x]
And what I've come up with so far in point-free notation:
foobar' = `map` [id, reverse] ($ x)
I can't seem to get that x off the end of there.
Others have already posted how you can do this using the Reader monad, but that's not the only way. It turns out that your second function is pretty close. I think you meant to post
foobar' x = (`map` [id, reverse]) ($ x)
Since the x is already near a rightmost position, you're almost there. First, transform the section ($ x) into a function, because it's a bit easier to work with:
-- by the definition of a right operator section
foobar'2 x = (`map` [id, reverse]) (\y -> ($) y x)
Next remove the x from the lambda body by bringing a new variable into scope, and applying the function to x
-- lambda abstraction I think...
foobar'2 x = (`map` [id, reverse]) $ (\z y -> ($) y z) x
Rewrite this application as a function composition, and then you can eta reduce:
-- by definition of '.'
foobar'3 x = (`map` [id, reverse]) . (\z y -> ($) y z) $ x
-- eta reduction
foobar'4 = (`map` [id, reverse]) . (\z y -> ($) y z)
Finally, notice that we can replace the lambda with a function
-- by definition of `flip`
foobar'5 = (`map` [id,reverse]) . flip ($)
and you have a point-free form.
You will be interested in the Applicative instance of the reader monad:
instance Applicative (e ->)
Using it you can easily distribute an argument:
liftA2 (+) sin cos 3
Here sin and cos are functions, which both receive the value 3. The individual results are then combined using (+). You can further combine this with the Category instance of (->), but of cource specialized versions of (.) and id are already defined in the Prelude.
Background: The Applicative instance for (e ->) really represents the SKI calculus, where (<*>) is the S combinator and pure is the K combinator. S is precisely used to distribute an argument to two functions:
S f g x = f x (g x)
It takes a function application (f g) and makes both dependent on the value x ((f x) (g x)).
Use sequence:
> let foobar' = sequence [id, reverse]
> foobar' "abcde"
["abcde","edcba"]
There are a few basic idiomatic combinators which pop up repeatedly, and are reimplemented with various higher concepts and libraries, but which are essentially very simple. Names may vary, and some are implementable in terms of others:
fork (f,g) x = (f x, g x) -- == (f &&& g)
prod (f,g) x = (f $ fst x, g $ snd x) -- == (f *** g)
pmap f (x,y) = (f x, f y) -- == (f *** f)
dup x = (x,x)
etc. Of course uncurry f (x,y) == f x y gets used a lot with these, too.
&&& and *** are defined in Control.Arrow, as well as first and second. Then prod (f,id) == first f, prod(id,g) == second g etc. etc.
So your foobar becomes
foobar = (\(a,b)->[a,b]) . fork (id,reverse)
= (\(a,b)->[a,b]) . (id &&& reverse)
= (\(a,b)->[a,b]) . (id *** reverse) . dup
= join $ curry ( (\(a,b)->[a,b]) . second reverse)
For the last one you need to also import Control.Monad and Control.Monad.Instances. See also this question.
late edit: also, using Control.Applicative as hinted in answer by ertes,
= (:) <*> ((:[]) . reverse)

Fusion law for foldr1?

For foldr we have the fusion law: if f is strict, f a = b, and
f (g x y) = h x (f y) for all x, y, then f . foldr g a = foldr h b.
How can one discover/derive a similar law for foldr1? (It clearly can't even take the same form - consider the case when both sides act on [x].)
You can use free theorems to derive statements like the fusion law. The Automatic generation of free theorems does this work for you, it automatically derives the following statement if you enter foldr1 or the type (a -> a -> a) -> [a] -> a.
If f strict and f (p x y) = q (f x) (f y)) for all x and y you have f (foldr1 p z) = foldr1 q (map f z)). That is, in contrast to you statement about foldr you get an additional map f on the right hand side.
Also note that the free theorem for foldr is slightly more general than your fusion law and, therefore, looks quite similar to the law for foldr1. Namely you have for strict functions g and f if g (p x y) = q (f x) (g y)) for all x and y then g (foldr p z v) = foldr q (g z) (map f v)).
I don't know if there's going to be anything satisfying for foldr1. [I think] It's just defined as
foldr1 f (x:xs) = foldr f x xs
let's first expand what you have above to work on the entire list,
f (foldr g x xs) = foldr h (f x) xs
for foldr1, you could say,
f (foldr1 g xs) = f (foldr g x xs)
= foldr h (f x) xs
to recondense into foldr1, you can create some imaginary function that maps f to the left element, for a result of,
f . foldr1 g = foldr1 h (mapfst f) where
mapfst (x:xs) = f x : xs

Why does the pointfree version of this function look like this?

I've been playing around with Haskell a fair bit, including practising writing functions in point-free form. Here is an example function:
dotProduct :: (Num a) => [a] -> [a] -> a
dotProduct xs ys = sum (zipWith (*) xs ys)
I would like to write this function in point-free form. Here is an example I found elsewhere:
dotProduct = (sum .) . zipWith (*)
However, I don't understand why the point-free form looks like (sum .) . zipWith (*) instead of sum . zipWith (*). Why is sum in brackets and have 2 composition operators?
dotProduct xs ys = sum (zipWith (*) xs ys) -- # definition
dotProduct xs = \ys -> sum (zipWith (*) xs ys) -- # f x = g <=> f = \x -> g
= \ys -> (sum . (zipWith (*) xs)) ys -- # f (g x) == (f . g) x
= sum . (zipWith (*) xs) -- # \x -> f x == f
= sum . zipWith (*) xs -- # Precedence rule
dotProduct = \xs -> sum . zipWith (*) xs -- # f x = g <=> f = \x -> g
= \xs -> (sum .) (zipWith (*) xs) -- # f * g == (f *) g
= \xs -> ((sum .) . zipWith (*)) xs -- # f (g x) == (f . g) x
= (sum .) . zipWith (*) -- # \x -> f x == f
The (sum .) is a section. It is defined as
(sum .) f = sum . f
Any binary operators can be written like this, e.g. map (7 -) [1,2,3] == [7-1, 7-2, 7-3].
KennyTM's answer is excellent, but still I'd like to offer another perspective:
dotProduct = (.) (.) (.) sum (zipWith (*))
(.) f g applies f on the result of g given one argument
(.) (.) (.) f g applies f on the result of g given two arguments
(.) (.) ((.) (.) (.)) f g applies f on the result of g given three arguments
...
Can do (.~) = (.) (.) (.), (.~~) = (.) (.) (.~), (.~~~) = (.) (.) (.~~) and now let foo a b c d = [1..5]; (.~~~) sum foo 0 0 0 0 results in 15.
But I wouldn't do it. It will probably make code unreadable. Just be point-full.
Conal's TypeCompose provides a synonym for (.) called result. Perhaps this name is more helpful for understanding what's going on.
fmap also works instead of (.), if importing the relevant instances (import Control.Applicative would do it) but its type is more general and thus perhaps more confusing.
Conal's concept of "fusion" (not to be confused with other usages of "fusion") is kind of related and imho offers a nice way to compose functions. More details in this long Google Tech Talk that Conal gave

Resources